COVID-19 Impact on Korean Films and Netflix Revenue - Sarjono, Haryadi; Gulzar, Ayesha; Nisa, Gadis Aura; Kok, Michelle; Nirbita, Shabira Zora; Silviya, Ine (Mahesa Research Center, 2025)
The COVID-19 pandemic has significantly affected the health, economic and social sectors, including the film industry. In 2020, the South Korean film industry experienced a 73.3% decline in revenue, from 226.68 million tickets sold in 2019 to only 59.52 million tickets after cinemas closed. In contrast, Netflix experienced an increase in the number of global subscribers by 16 million in the first quarter of 2020. The South Korean film industry adapted to this condition through various strategies, including releasing films directly to streaming platforms, collaborating with Netflix for content distribution, and adjusting production budgets to maintain industry expectations. In comparison, similar trends are occurring in Hollywood and Europe, where the film industry is turning to video-on-demand services as a primary distribution alternative. This study analyzes the impact of the pandemic on the South Korean film industry and Netflix's role in maintaining the existence and profitability of this sector amidst the global crisis.